Пошаговое объяснение:
(8х-1)^2-25=64х^2-16х+1-25=
=64х^2-16х-24=64×(1/12)^2-16×1/12-24=
=64×1/144-4/3-24=4/9-4/3-24=
=(4-12-216)/9= - 224/9= - 24 8/9
Б)
(9х-3)^2-12(х-3)+36=
=81х^2-54х+9-12х+36+36=
=81х^2-66х+81=81×(9,3)^2-66×9,3+81=
=81×86,49-613,8+81=7005,69-613,8+81=
=6472,89
Пошаговое объяснение:
(8х-1)^2-25=64х^2-16х+1-25=
=64х^2-16х-24=64×(1/12)^2-16×1/12-24=
=64×1/144-4/3-24=4/9-4/3-24=
=(4-12-216)/9= - 224/9= - 24 8/9
Б)
(9х-3)^2-12(х-3)+36=
=81х^2-54х+9-12х+36+36=
=81х^2-66х+81=81×(9,3)^2-66×9,3+81=
=81×86,49-613,8+81=7005,69-613,8+81=
=6472,89